Bedeutung, Gebrauch und sprachliche Handlung. Ansätze und Probleme einer handlungstheoretischen Semantik aus linguistischer Sicht - Gloning, Thomas (Reihe Germanistische Linguistik, 1996)
The meaning of expressions in a language is equivalent to the way they are used in a given language community. Views of this nature are central to the assumptions underlying 'usage theories of meaning' and 'action-theoretical semantics'. The first major section of the book provides an overview of approaches to establishing an action-theoretical semantics and the productive aspects these approaches have engendered (Wittgenstein, ordinary language philosophy, speech-act theory, the discussion sparked off by Grice, game-theoretical semantics, philologically oriented semantics etc.). The second major part is given over to a discussion of central problems of action-theoretical semantics (fundamental concepts, truth-conditions and use-conditions, compositional meaning, forms of meaning description, literal meaning and variety of uses etc.).